Surface energy partitioning and evapotranspiration in a Pinus tabuliformis plantation in Northeast China - Gao, Xiang; Zhang, Jinsong; Cai, Jinfeng; Pei, Songyi; Liu, Linqi; Meng, Ping; Huang, Hui (Frontiers in Plant Science, 2023)
Examining the land-atmosphere interaction in vegetation rehabilitation areas is important for better understanding of land surface processes affected by human activities. In this study, energy flux observations were used to investigate surface energy partitioning and evapotranspiration (ET) in a Pinus tabuliformis plantation in Northeast China in 2020 and 2021. The sensible heat flux (H) was the dominant component of Rn, and the ratio of H to the latent heat flux was higher than 1 at all growth stages. The two most important factors influencing the midday evaporative fraction and daily ET were the normalized difference vegetation index (NDVI) and soil water content at 10 cm depth (SWC10). Cumulative precipitation (P) minus ET was 62.83 and 239.90 mm in 2020 (annual P of 435.2 mm) and 2021 (annual P of 632.8 mm), respectively. The midday Priestley–Taylor coefficient (α), surface conductance (gs), and decoupling coefficient increased gradually from the onset of the mid-growing stage and decreased from the later growing stage. Midday α and gs increased with NDVI and SWC10 increasing until the NDVI (0.5) and SWC10 (0.17 mm3 mm−3) thresholds were reached, respectively. Midday α and gs were significantly influenced by vapor pressure deficit below 3 kPa, and the threshold value of midday gs was approximately 12 mm s−1. In conclusion, this Pinus tabuliformis plantation regulated surface energy partitioning properly, and left a part of P for surface runoff and groundwater recharge in the semiarid region of Northeast China.